Dobro dziecka a kolejne nowelizacje Kodeksu rodzinnego i opiekuńczego - Stojanowska, Wanda; Kosek, Mirosław (Ius Matrimoniale, 2018)
This article aims to analyse the recent amendments to the Family and Guardianship Code (of 6 November 2008 and 25 June 2015) from the point of view of child’s welfare. The aim of the analysis is to determine the impact of the introduced normative solutions on the extent of protection of this welfare. The analysis covers those family laws and regulations, which by their very nature pose the greatest threat to the child’s welfare, i.e. the divorce law, with particular emphasis on the method of exercising parental authority after divorce and maintaining contact with the child. The analyses have led the authors to the conclusion that the provisions of Article 58 of the Family and Guardianship Code introduced by the amendment of 25 June 2015 result in a significant limitation of the extent of child welfare protection. The adoption, as a rule, of a resolution based on awarding parental authority over their underage children to both divorced parents, in each individual case, regardless of the existence of a conflict between them, and consequently the introduction of the so-called joint alternate custody as a model solution, poses a serious threat to the child’s welfare.